2010
DOI: 10.1113/jphysiol.2010.195511
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid type-1 (TRPV-1) channels contribute to cutaneous thermal hyperaemia in humans

Abstract: The initial, rapid increase in skin blood flow in response to direct application of heat is thought to be mediated by an axon reflex, which is dependent on intact cutaneous sensory nerves. We tested the hypothesis that inhibition of transient receptor potential vanilloid type 1 (TRPV-1) channels, which are putative channels located on sensory nerves, would attenuate the skin blood flow response to local heating in humans. Ten subjects were equipped with four microdialysis fibres which were randomly assigned on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 33 publications
(85 reference statements)
3
113
3
Order By: Relevance
“…Our laboratory has shown previously this vehicle of 90% propylene glycol in 10% lactated Ringer does not result in vasodilation (i.e., there is no baseline shift), and 20 mM capsazepine significantly attenuates the initial peak phase of cutaneous thermal hyperemia in response to local heating (29). We, and others, have previously shown that a 10 mM concentration of L-NAME adequately inhibits NO synthase in human skin (7, 10, 20, 28, 30 -33).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our laboratory has shown previously this vehicle of 90% propylene glycol in 10% lactated Ringer does not result in vasodilation (i.e., there is no baseline shift), and 20 mM capsazepine significantly attenuates the initial peak phase of cutaneous thermal hyperemia in response to local heating (29). We, and others, have previously shown that a 10 mM concentration of L-NAME adequately inhibits NO synthase in human skin (7, 10, 20, 28, 30 -33).…”
Section: Methodsmentioning
confidence: 95%
“…All drugs were infused for at least 60 min before commencement of whole body heating (10,28,29). To initiate whole body heating, subjects were covered with a plastic water-impermeable rain suit to minimize evaporative heat loss, and 50°C water was circulated through the water-perfused suit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study did not directly investigate TRP channels, they are considered to be heat sensing and, more importantly, pain sensing. Recently, Wong & Fieger (2010) reported that TRPV1 channels contributed to the cutaneous thermal hyperaemia response in skin. Thus, a painful heat stress localized to a small area of skin, as used in the present study, might induce an autonomic response via TRPV1 stimulation, causing a rapid and exaggerated vasodilator response.…”
Section: Sensory Nervesmentioning
confidence: 99%
“…This notable feature suggested a significant role for thermally sensitive afferents in the forearm dermis. More recently, Wong & Fieger (2010) determined that transient receptor potential vanilloid type 1 (TRPV1) channels localized within sensory afferents contribute greatly to the initial peak and nadir of the hyperaemic response. Much of the work investigating TRP channels has identified a subfamily of vanilloid receptors with pain-and heat-sensing capabilities, yet their individual activation thresholds exhibit clear distinctions Willis, 2009).…”
Section: Sensory Nervesmentioning
confidence: 99%